Strategi Pengembangan Potensi Sumber Daya Alam melalui Eduwisata Bumi Perkemahan Panglima Batur Trahean Kabupaten Barito Utara - Wardani, Ahmad (IAI Nasional Laa Roiba Bogor, 2024)
Trahean Muara Teweh North Barito Town has the potential for normal assets, HR and socio-social assets that help endeavors to incorporate estate, fishery and the travel industry organizations. Buper Panglima Batur has many supporting offices, for example, diversion stages, privileged stages, stately fields, structures, petitioning God rooms, seeing pinnacles, wharfs, prepared to-hydrate offices, and gazebos for unwinding. This exploration means to decide the travel industry potential in light of financial and biological examinations and to figure out the administration endeavors and advancement techniques of the Trahean Camping area region, as well as expanding vacationer visits and neighborhood local area pay. The exploration strategy utilized by the creator is subjective examination. The information assortment methods utilized in this study are through direct perception, interviews, archive recording, and diary articles. In view of the consequences of the examination, this study shows that Trahean village has an exceptionally unprecedented the travel industry potential, be it regular the travel industry or counterfeit the travel industry. Nonetheless, enhancements are as yet required in a few areas to make a protected and agreeable environment for the travel industry exercises in Trahean village.